Supersymmetric gauge theory: an application of group theory in high energy physics and starobinsky model of cosmological ination - Upoma, Ipshita Bonhi (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics, 2016